Dwell time stability and stabilization of interval discrete-time switched positive linear systems. (August 2019) - Li, Yang; Zhang, Hongbin
Abstract: This paper investigates the dwell time stability and stabilization problems of discrete-time switched positive linear systems (DSPLSs) with interval uncertainties. The dwell time refers to constant dwell time, ranged dwell time and minimum dwell time. At first, some sufficient conditions are presented for the dwell time stability of primal and transpose interval DSPLSs. Meanwhile, the conservatisms of these conditions are compared. Then, equivalent stabilization conditions are presented for interval DSPLSs with dwell time. The controller gain matrices can be computed by solving the convex lifted conditions directly. All the results are given in terms of linear programming (LP). At last, several numerical examples verify the correctness and significance of the results.